Effect of family-school training on improving positive parenting - Lathifah Khaerunnisa (Himpunan Pengembang Kurikulum Indonesia, 2026)
Family School is a short-term educational and training program that helps parents learn about behavioral changes and the formation of children's personalities, guided by parents, to improve the quality of childcare within the family. This study aims to determine the effectiveness of the training implemented by analyzing the influence of the reaction rate, learning rate, and level of behavioral change after the training on family care among participants. The sample consisted of 30 participants who had attended the training. Data collection techniques used survey studies and documentation, with multiple regression analysis. The study found three independent variables (reaction rate, learning rate, and level of behavioral change) suspected of influencing the level of positive parenting in families after attending the training, and all had a significant effect simultaneously. This suggests that the training held so far can change behavior, thereby increasing family quality. What needs to be studied further is the selection of training participants, so that the implementation of family school can be more effective. Abstrak Sekolah Keluarga merupakan proses pendidikan dan pelatihan jangka pendek untuk mempelajari pengetahuan mengenai perubahan tingkah laku atau pembentukan kepribadian anak dalam keluarga yang diikuti oleh para orang tua guna memperbaiki atau meningkatkan kualitas pengasuhan anak di keluarga. Penelitian ini bertujuan untuk mengetahui efektivitas pelatihan yang telah dilaksanakan dengan melakukan analisis pengaruh tingkat reaksi, tingkat pembelajaran dan tingkat perubahan perilaku pasca pelatihan terhadap pengasuhan keluarga bagi para peserta. Sampel terdiri dari 30 peserta yang telah mengikuti pelatihan. Teknik pengumpulan data menggunakan studi survei dan dokumentasi dengan teknik analisis regresi berganda. Hasil penelitian menemukan tiga variabel independen (tingkat reaksi, tingkat pembelajaran, tingkat perubahan perilaku) yang diduga mempengaruhi tingkat pengasuhan positif dalam keluarga sesudah mengikuti pelatihan ternyata secara simultan berpengaruh signifikan. Hal tersebut mengisyaratkan bahwa pelatihan yang selama ini diadakan mampu mengubah perilaku, sehingga tingkat kualitas keluarga meningkat. Adapun yang perlu diteliti lebih dalam adalah pemilihan peserta pelatihan, sehingga pelaksanaan sekolah keluarga dapat lebih efektif. Kata Kunci: pelatihan anak; pengasuhan positif; sekolah keluarga